STRUKTUR DAN KEBAHASAAN TEKS CERITA FANTASI KARYA SISWA KELAS VII SMP PEMBANGUNAN LABORATORIUM - Putri, Finny Rizkyah; Thahar, Harris Effendi; Arief, Ermawati (Universitas Negeri Padang, 2018)
The aim of the research is to be describe these following two things. First, to describe the structure of story text written by seventh grade students in Junior High School Pembangunan Laboratorium UNP. Second, to describe the text of the fantasy story of studentsâ€™ works. The method that is used is descriptive method. This research was done in Junior High School Pembangunan Laboratorium UNP. the data of the research are fantasy story texts collected in many sources such as the documents of 20 fantasy text stories written by the students. Instrument of this research is the writer herself. The data was analyzed by describing the data, than analyzing and discussing them towards the theory. The result of the research is, first, there are three generic structures of fantasy story, they are, orientation, complication, and resolution in the works of the students in Junior High School Pembangunan Laboratorium UNP. the second result is there are 273 accuracies of the sentence use and EBI, there are 341 inaccuracies, and 7282 diction accuracy (selected word), and 62 diction inaccuracy (selected word) in the studentsâ€™ writings. Based on this research, it can be concluded that, the students are able to use the generic structures correctly. It is proved by 20 texts that have been analyzed, and there are 18 texts that use all generic structures correctly. Then, the students are more skillful in using diction (selected word) in their writing than sentences and EBI.Â Kata kunci: struktur teks, kebahasaan teks, teks cerita fantasi